Persistence of haemostatic response following gene therapy with valoctocogene roxaparvovec in severe haemophilia A. Issue 6 (11th August 2021) - Pasi, K John; Laffan, Michael; Rangarajan, Savita; Robinson, Tara M; Mitchell, Nina; Lester, Will; Symington, Emily; Madan, Bella; Yang, Xinqun; Kim, Benjamin; Pierce, Glenn F; Wong, Wing Yen
Abstract: Introduction: Valoctocogene roxaparvovec is an investigational AAV5‐based factor VIII (FVIII) gene therapy that has demonstrated sustained clinical benefit in people with severe haemophilia A. Aim: To report safety, tolerability, efficacy, and quality of life (QOL) among participants who received valoctocogene roxaparvovec in a phase 1/2 clinical study (NCT02576795). Methods: Men ≥18 years of age with severe haemophilia A (FVIII ≤1 IU/dl) without history of FVIII inhibitors or anti‐AAV5 antibodies received a single infusion of valoctocogene roxaparvovec and were followed for 5 years (6 × 10 13 vg/kg dose, n = 7) and 4 years (4 × 10 13 vg/kg dose, n = 6). Results: Over the past 2 years, few adverse events and no FVIII inhibitors were reported. Per chromogenic substrate (CSA) assay at years 5 and 4, four of seven and three of six participants in the 6 × 10 13 and 4 × 10 13 vg/kg cohorts, respectively, maintained median FVIII levels >5 IU/dl, corresponding to mild haemophilia. By regression analysis, rate of change in FVIII activity was ‐0.14 (95% confidence interval [CI]: ‐.32 to .03) IU/dl/wk in the 6 × 10 13 vg/kg cohort in year 5 and ‐.06 (95% CI: ‐.14 to .01) IU/dl/wk in the 4 × 10 13 vg/kg cohort in year 4. No participants resumed FVIII prophylaxis, and eight of 13 participants reported zero bleeds in the past 2 years. Improved QOL from baseline persisted in the 6 × 10 13 vg/kg cohort; all six Haemo‐QOL‐A domain scores increased. For the 4 × 10 13 vg/kg cohort, high baseline Haemo‐QOL‐A scores persisted. Conclusion: These results demonstrate transgene expression and haemostatic response for up to 5 years in individuals with haemophilia A.